2017
DOI: 10.5746/leia/17/v8/i1/a06/nguyen
|View full text |Cite
|
Sign up to set email alerts
|

Does Dictogloss Improve Non-English Major Students’ Motivation and Grammatical Competence?

Abstract: This 12-week research examined the effects of dictogloss on the students' grammatical competence and motivation. Data were collected through tests, questionnaires, and observation involving twenty eight students in a maths classat a higher education institution in Vietnam. The initial data indicated that students had low grammatical competence and motivation in learning grammar. By analyzing the textbook, the researcher found out it was structured in a way where dictogloss could be applicable and then an actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…During dictogloss procedures learners are able to deal with the language through a cooperative writing activity. In line with Hang Nguyen (2017), the researcher also observed that through this collaboration, weaker learners were able to complete the activities, which were difficult to deal with in the absence of the abovementioned procedure in the first place, by learning from stronger ones who could actively lead and support the group. Cooperation also encouraged them to reflect on form and to take risks after thinking critically about their language use.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…During dictogloss procedures learners are able to deal with the language through a cooperative writing activity. In line with Hang Nguyen (2017), the researcher also observed that through this collaboration, weaker learners were able to complete the activities, which were difficult to deal with in the absence of the abovementioned procedure in the first place, by learning from stronger ones who could actively lead and support the group. Cooperation also encouraged them to reflect on form and to take risks after thinking critically about their language use.…”
Section: Discussionmentioning
confidence: 76%
“…As was emphasized by Nguyen (2017), four levels of dictogloss need pre-teaching to prevent misunderstanding of the text. Therefore, the researcher carried out a rehearsal for training each level of dictogloss procedure, including the ability to take notes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies have employed dictogloss to teach different aspects of language. For example, dictogloss has been shown to be useful in teaching grammar (Nguyen, 2017;Qin, 2008;Rashtchi & Khosroabadi, 2008), in promoting the writing ability of English language learners (e.g., Bataineh & Bani Younis, 2016;Murad, 2017), dictation (e.g., Faghani, Derakhshan, & Zangoei, 2015), and listening comprehension (e.g., Marashi & Khaksar, 2013;Vasiljevic, 2010).…”
Section: Jigsaw and Dictogloss Tasksmentioning
confidence: 99%